Identificando Clusters. Uma Proposta Metodológica com Aplicação Empírica ao Sector do Turismo
The goal of this thesis was to analyse clusters as systems that stimulate interaction and synergies among its members as well as productivity and competitiveness gains. Given the vast area to which this concept is applied to and also the immense number of studies already put forward, we focus on analysing tourism and its potentialities in terms of clustering. Tourism Industry s significance in terms of job creation is increasing among the European countries and on a regional level, tourism as come up as a driving force for economic growth and development. The geographical concentration of tourism related activities has often led to an abusive use of the term cluster to describe these regional concentrations. In fact, many studies that identify clusters in general, and tourism clusters in particular, are based in a simplistic analysis of location quotients or experts opinions neglecting a fundamental aspect of the cluster concept, the linkages between agents. Thus, this results in an over identification of clusters, in general and tourism clusters in particular. Using the existing literature on Regional Economics and Tourism Economics as a departure point, the elements crucial to having a tourism cluster are defined: agglomeration and significant linkages. From this conceptualization, we propose a general quantitative methodology to identify clusters, which is afterwards tested on the NUT II Algarve in order to evaluate if there might be a tourism cluster in that region. In accordance to the results obtained regarding the agglomeration indicators used (location quotient and specialization coefficient) and the methods applied to analyse Algarve s input-output matrix (M-Method and the Diagonalization Method) and evaluate the depth of the linkages, we conclude that, Algarve can hardly be considered a cluster. At best, and taking in consideration just the results of the agglomeration indicators used, we may say that Algarve may have a Tourism cluster on a relatively narrow segment of hotels Villages and Apartments. However, the lack of significant density of linkages between Tourism s core activities does not allow us to validate the existence of a Tourism cluster.